A new perceptual paradigm to investigate the visual remapping of others’ tactile sensations onto one’s own body shows “mirror touch” for the hands - Gillmeister, Helge (Frontiers in Psychology, 2014)
The last two decades have seen a multitude of publications showing the activation of an observer's somatosensory cortical system during the observation of touch on another person. Behavioural demonstrations of "mirror touch", however, have been slow in coming forward, and have so far primarily been shown as “visual remapping of touch” on the face. The present study uses a new paradigm to investigate the mirroring of others’ tactile sensations: a 2-AFC task of intensity judgment for touch on the observer's left and right index finger pads. Observers viewed a left and right hand in an egocentric position, which were either touched passively (pencil moving to touch index finger pad) or actively sought touch (index finger moving to touch pencil). Touch and no-touch events for the two viewed hands were designed to eliminate confounding effects of spatial attention. Felt touches were either concurrent with viewed touch or no-touch events, or were delayed in time to assess potential response bias. The findings demonstrate visual remapping of touch for touch on the hands. If touch was shown on one of the hands only (e.g. left), observers were more likely to perceive touch on the same hand (ie. their own left hand) as more intense than touch on the other hand even if tactile intensities did not differ, compared to touch shown on both or neither hand. These remapping effects occurred only when viewed and felt touches were concurrent, they were strongly modulated by the way in which viewed touch was incurred, and they were more reliable for touch on the left hand. A second, control experiment, in which touch observation was replaced by bright dots shown on or next to the finger pads, confirmed that these effects were largely due to genuine tactile mirroring rather than to somatotopic cueing. This 2-AFC tactile intensity judgment task may be a useful paradigm to investigate the remapping of others’ tactile sensations onto an observer's own body.